EFEKTIVITAS PELATIHAN KEPEMIMPINAN ADMINISTRATOR (PKA) OLEH BADAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH (BPSDMD) PROVINSI SUMATERA SELATAN - Shakila, Chika Derri Felicia; Waliah, Siti; Yuliana, Yuliana; Suandi, Suandi (MAP Program Pascasarjana Universitas Sjakhyakirti, 2024)
The Regional Human Resources Development Agency (BPSDMD) of South Sumatra Province is a government agency that organizes training, one of them is Administrator Leadership Training (PKA). Administrator Leadership Training aims to develop performance managerial leadership competencies to ensure the implementation of accountability for administrator level or echelon III positions. The identification of problems found was that the implementation of Administrator Leadership Training (PKA) was not optimal and the number of classes and participants was fluctuated. The aim of this research is to determine the effectiveness of Administrator Leadership Training (PKA) by the Regional Human Resources Development Agency (BPSDMD) of South Sumatra Province. This research uses a descriptive method with a qualitative approach so that it can explain in detail of the phenomena. The results of this research show that the implementation of Administrator Leadership Training (PKA) by the Regional Human Resources Development Agency (BPSDMD) of South Sumatra Province has been carried out well in accordance with applicable regulations and can be applied well by participants. Fluctuations of the number in classes and participants occurred due to refocusing or budget reductions from the South Sumatra Provincial Government.